Childhood maltreatment moderates the influence of genetic load for obesity on reward related brain structure and function in major depression. (February 2019) - Opel, Nils; Redlich, Ronny; Repple, Jonathan; Kaehler, Claas; Grotegerd, Dominik; Dohm, Katharina; Zaremba, Dario; Goltermann, Janik; Steinmann, Lavinia-Alexandra M.; Krughöfer, Rahel; Leehr, Elisabeth J.; Böhnlein, Joscha; et al.
Highlights: Childhood maltreatment moderated the association between polygenic risk for obesity and body mass index. Childhood maltreatment and polygenic risk interacted on gray matter and BOLD response in reward related brain regions. Our findings highlight the influence of maltreatment and polygenic risk on neurobiological correlates of obesity in MDD. Abstract: Obesity is a clinically relevant and highly prevalent somatic comorbidity of major depression (MDD). Genetic predisposition and history of childhood trauma have both independently been demonstrated to act as risk factors for obesity and to be associated with alterations in reward related brain structure and function. We therefore aimed to investigate the influence of childhood maltreatment and genetic risk for obesity on structural and functional imaging correlates associated with reward processing in MDD. 161 MDD patients underwent structural and functional MRI during a frequently used card guessing paradigm. Main and interaction effects of a polygenic risk score for obesity (PRS) and childhood maltreatment experiences as assessed using the Childhood Trauma Questionnaire (CTQ) were investigated. We found that maltreatment experiences and polygenic risk for obesity significantly interacted on a) body mass index b) gray matter volume of the orbitofrontal cortex as well as on c) BOLD response in the right insula during reward processing. While polygenic risk for obesity was associated with elevated BMI as well as with decreased OFC gray matter and increased insular BOLD response in non-maltreated patients, these associations were absent in patients with a history of childhood trauma. No significant main effect of PRS or maltreatment on gray matter or BOLD response could be detected at the applied thresholds. The present study suggests that childhood maltreatment moderates the influence of genetic load for obesity on BMI as well as on altered brain structure and function in reward related brain circuits in MDD.